Evaluation of the level of knowledge of arterial hypertension and cardiovascular risk factors in people who attend to Corrales health center. Tumbes. Peru. 2007 - Lilia Jannet Saldarriaga Sandoval (Fundación para el Desarrollo de la Enfermería, 2010)
The present is a simple descriptive study to determine the level of knowledge of arterial hypertension and factors of cardiovascular risk in adult people who attend to the health center Corrales from February to October in 2007.The sample thus was composed by 48 adult people between 35 to 65 years classified by being the cases brought (reported) by the office of statistics grouped according to occupation like that we have: farmers, workers, and housewives who were asked were answering the questionnaire that was containing the independent variables: factors of cardiovascular risk and knowledge on arterial hypertension, and that were expiring with the criteria of incorporation and exclusion.Deciding that the knowledge is low in 45.8 %en the majority of the studied population, these do not know the factors of cardiovascular risk, 35 % of the persons has knowledge that the obesity is a factor of cardiovascular risk, 62.8 % of the masculine sex; the patients prevailed from 60 to 65 years, between(among) the harmful habits the consumption of cigarette with 25 % and alcohol with 29 % the risk is at least the double, in comparison with not smokers there being obtained that are reasons more common in the cardiac diseases and with it the presence of hypertensive disease.